Soccer and chilean Cinema: imaginary, stereotypesand narrative identities - Marín Naritelli, Francisco (Folios, revista de la Facultad de Comunicaciones y Filología, 2013)
The aim of this article is to map the different narratives present in the Chilean film productions around soccer. In fiction: “Historias de Fútbol” (1997) and “Azul y Blanco” (2004) and in the documentary: “Raza Brava” (2007) and “Ojos Rojos” (2010). A critical analysis of the cinematic speech has been proposed as a perception, social imagery, identity and stereotype producer and replicator. Among the conclusions can be established that the imaginary set around soccer, mobilized by the Chilean cinema, reiterates a space of social recognition and identity construction within the realm of the present, and, in the case of the national team, is a symbolic remain of national identity.